MANAJEMEN EVENT PAGELARAN KESENIAN REOG DALAM MEWUJUDKAN TOURISM SUPPLY CHAIN DI KABUPATEN PONOROGO - Johan Bhimo Sukoco; Wulan Kinasih; Maya Sekar Wangi; Aris Tri Haryanto (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2022)
Ponorogo Regency is known as Reyog City. Reyog art has become an inherent brand and has been internalized in the daily life of people in Ponorogo Regency. Ponorogo Regency has 367 Reyog Associations spread in various remote villages and sub-districts. This quantity is a great potential in developing logistics governance in the tourism sector in the district. However, often reyog performances held at the village/kelurahan level do not pay attention to rules, such as the lack of publications, which results in this event being less well known by tourists, both domestic and foreign. This study aims to describe and analyze the stages of event management in reyog performances in Ponorogo Regency. Researchers studied it with the event management approach proposed by Goldblatt (2014), covering 5 (five) stages, namely: research, design, planning, coordination, and evaluation. In this study, the Likert Scale was used to measure respondents' perceptions of the organization of the event. The number of respondents in this study were 23 people, consisting of spectators and performers of art performances. The results showed that in general, Reyog art performances in Ponorogo Regency had fulfilled the five stages of event management. However, there are still some stages that are not optimal, so that in the future more attention needs to be paid, such as the need for mapping the needs of the audience in the research stage, increasing promotions in the coordination stage, to the opportunity for the audience to provide criticism and suggestions in the evaluation stage.